2020
DOI: 10.20882/adicciones.1329
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la eficacia de WhatsApp en un programa grupal de reducción de daños asociados al consumo inyectado de drogas

Abstract: ResumenAbstract original adicciones vol. xx, nº x · 2020 El presente estudio analiza el uso de una aplicación de mensajería instantánea (WhatsApp®) como canal de acceso a personas que se inyectan drogas. Se diseñó un estudio observacional longitudinal prospectivo de ocho semanas y tres observaciones en cinco centros de adicciones en Cataluña. Participaron 105 personas que consumían drogas por vía parenteral, distribuidas en cinco grupos de intervención grupal. Se compararon los resultados de la escala Risk Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(37 reference statements)
0
2
0
2
Order By: Relevance
“…Educational and psychological interventions destined to socially excluded people show psychological benefits on their own (Calvo and Carbonell 2018). Thus, Calvo et al (2020) also demonstrated WhatsApp's efficacy on health intervention in his study, describing two main lessons extracted from his work. All patients that finished the process reported that they would be willing to participate periodically in virtual groups or continuously as part of their therapeutic process.…”
Section: Intervention Studies On Injectable Drug Usersmentioning
confidence: 90%
“…Educational and psychological interventions destined to socially excluded people show psychological benefits on their own (Calvo and Carbonell 2018). Thus, Calvo et al (2020) also demonstrated WhatsApp's efficacy on health intervention in his study, describing two main lessons extracted from his work. All patients that finished the process reported that they would be willing to participate periodically in virtual groups or continuously as part of their therapeutic process.…”
Section: Intervention Studies On Injectable Drug Usersmentioning
confidence: 90%
“…Szacuje się, że ok. 96 mln, czyli 29%, dorosłych (w wieku od 15 do 64 lat) w Unii Europejskiej przynajmniej raz w życiu spróbowało narkotyków. Według szacunków w 2018 roku narkotyki zażyło 19,1 mln (16%) osób dorosłych (w wieku [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], przy czym było wśród nich ok. dwukrotnie więcej mężczyzn (20%) niż kobiet (11%) [30]. W świetle przeprowadzonych badań najwięcej ankietowanych (44%) sięgnęło po raz pierwszy po narkotyki w domu [31].…”
Section: Dyskusjaunclassified
“…Na świecie wciąż poszukuje się nowych sposobów pozyskania zaufania osób uzależnionych, by pomóc im zwalczyć nałóg. F. Calvo opisuje skuteczność szybkiej komunikacji z nimi poprzez aplikację WhatsApp® inter-Vention w celu zmniejszenia ryzyka zakażenia HIV i szkód wywołanych zażywaniem substancji nieznanego pochodzenia lub zanieczyszczonych chemicznie [34]. Osoby uzależnione mogą szybko skomunikować się w ten sposób z personelem ośrodków, jak i w grupach, i uzyskać pomoc.…”
Section: Dyskusjaunclassified
“…Though some studies have been conducted of chat apps as drug purchasing channels (Moyle et al, 2019) or a means of supporting needle exchange programs (Calvo et al, 2020), there appear to have been no studies of mobile chats hosting spontaneous peer-led harm reduction communities. This study thus analyzes chat conversations among peers and between users and netreach workers in order to provide insights to professionals wishing to implement harm reduction interventions on chat apps.…”
Section: Introductionmentioning
confidence: 99%